2021
DOI: 10.22271/allresearch.2021.v7.i7a.8731
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual review on krimiroga in ayurveda

Abstract: The Ayurveda combines the Sanskrit words Ayu (life) and Veda (science or knowledge) thus Ayurveda means science of life. Ayurveda is a traditional system of medicine having emergence a thousand year ago. Since that ancient time Ayurvedic Aacharyas were well known by existence of Krimis, and they have mentioned it in their various literatures regarding its Nidana (causes), Sankhya (different number), Naamkarana (terminology), Swarupa (appearance), Lakshana (symptoms), Sthana (finding area) Chikitsa Vyavastha (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Although hemodialysis can help restore the functional ability of the kidneys, hemodialysis can also cause various complications. Some previous research results showed hypoxemia occurred in 10% of kidney failure patients undergoing hemodialysis (Campos et al, 2016;Meyring-Wösten et al, 2016;Palamidas et al, 2014), with a decrease in PaO2 by 10-20 mmHg during hemodialysis (Sonkar et al, 2016). Intradialytic arterial oxygen saturation and low central venous oxygen saturation in hemodialysis patients indicate an imbalance between upper body systemic oxygen supply and demand, which is at risk of increasing mortality (Kooman et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Although hemodialysis can help restore the functional ability of the kidneys, hemodialysis can also cause various complications. Some previous research results showed hypoxemia occurred in 10% of kidney failure patients undergoing hemodialysis (Campos et al, 2016;Meyring-Wösten et al, 2016;Palamidas et al, 2014), with a decrease in PaO2 by 10-20 mmHg during hemodialysis (Sonkar et al, 2016). Intradialytic arterial oxygen saturation and low central venous oxygen saturation in hemodialysis patients indicate an imbalance between upper body systemic oxygen supply and demand, which is at risk of increasing mortality (Kooman et al, 2021).…”
Section: Discussionmentioning
confidence: 98%